Effects of l-carnitine on gilt growth, fetal growth and fetal muscle characteri[s]tics, and the IFG system in pigs harvested at day 40, 55, and 70 of gestation - Brown, Kelly Rae (Kansas State University, 2006)
We used a total of fifty-nine gilts (BW=137.7 kg) from three different breeding groups were used to assess the effects of feeding L-carnitine during gestation on gilt growth characteristics, gilt and fetal blood metabolites, litter characteristics, and IGF axis components in fetal hepatic and skeletal muscle, maternal uterine and chorioallantois tissues, and porcine embryonic myoblasts collected from fetuses. Experimental treatments were arranged in a 2 × 3 factorial arrangement with main effects of L-carnitine and day of gestation. Gilts were fed a constant feed allowance of 1.75 kg/d and a top-dress containing either 0 or 50 ppm of L-carnitine starting on the first day of breeding through the allotted gestation length (40, 55, or 70). No differences (P > 0.16) were observed for BW or estimated protein or fat mass at any gestation length. Gilts fed L-carnitine tended to have greater (P = 0.10) backfat at d 40 and were numerically heavier at d 70 compared to control gilts. No differences (P > 0.77) were observed in circulating total and free carnitine at breeding, but concentrations increased (P < 0.01) as gestation length increased for the gilts fed L-carnitine compared to those fed the control diet. Fetuses from the gilts fed L-carnitine tended to be heavier (P = 0.06) and fetal circulating IGF-II lower (P = 0.09) at day 70 compared to the fetuses from the control gilts. Insulin-like growth factor-I (IGF-I) mRNA was lower (P = 0.05) in fetal hepatic tissue in fetuses collected from gilts fed supplemental L-carnitine. Insulin-like growth factor binding protein-3 (IGFBP-3; P = 0.05) and IGFBP-5 mRNA increased (P = 0.01) and IGF-I mRNA numerically increased (P = 0.16) in the endometrium of gilts supplemented with L-carnitine. At d 55 or 70 gestation, fetuses were removed for collection of porcine embryonic myoblasts (PEM) from the semitendinosus. There were no treatment differences (P > 0.10) for the expression of IGF-I, IGF-II or IGFBP-5 mRNA levels. However, PEM isolated from fetuses collected from gilts fed L-carnitine had lower (P = 0.08) IGFBP-3 mRNA levels compared to the controls. Myoblasts isolated from fetuses obtained from gilts fed L-carnitine had greater (P = 0.09; 8.8 %) 5.1H11 monoclonal antibody attachment after 72 h in culture. Although not significant (P = 0.20), the total number of PEM in the S phase of the cell cycle was 4.7 % greater in PEM collected from fetuses from gilts fed L-carnitine compared to the controls. This study shows L-carnitine supplementation to gestating gilts has beneficial effects on average fetal weight, due in part to changes in the expression of the IGF axis at the fetal-maternal interface in swine. These changes in the IGF axis play a fundamental role in porcine fetal growth and development due to enhanced proliferation and delayed differentiation of PEM.
Keywords: pigsInsulin-like growth factor; Insulin-like growth factor binding protein; L-carnitine; Messenger RNA; Myoblasts; Agriculture, Animal Culture and Nutrition (0475)